Evaluation of Optical Coherence Tomography Angiography in Degenerative and Tractional Lamellar Macular Hole - Burcu Polat Gültekin; Defne Kalaycı (Journal of Ophthalmology)
Background. This study aims to evaluate the optical coherence tomography angiography (OCTA) findings in cases with degenerative and tractional lamellar macular holes (LMH). Methods. Two subtypes of LMH cases were included. Seventeen patients had the degenerative subtype, whereas 18 patients had the tractional subtype of LMH. Twenty healthy individuals were enrolled as the control group. The foveal avascular zone (FAZ) and retinal vascular densities in the superficial, deep capillary, and choriocapillary plexuses were analyzed and compared with fellow eyes and healthy controls using OCTA. Results. The mean FAZ area was wider in the degenerative subtype (0.33 ± 0.14 mm2) compared to the tractional subtype (0.24 ± 0.10 mm2) (p=0.04) and control eyes (0.26 ± 0.10 mm2) (p=0.03). Foveal vessel densities in the superficial and deep capillary plexuses were lower in the degenerative group than in the tractional group, (21.7 ± 9.8% vs. 26.8 ± 6.9%, p=0.01 and 28.5 ± 5.1% vs. 36.9 ± 6.2%, p=0.01). Choriocapillary vascular density in the parafoveal area was also lower in degenerative lamellar macular holes compared to the tractional group (60.4 ± 4.7% vs. 63.7 ± 3.9%, p=0.03). Compared to control eyes, eyes with degenerative and tractional LMH showed lower vessel densities in the parafoveal and perifoveal areas of the SCP, DCP, and all layers of CC (p<0.05). In the foveal area, the LMH groups showed higher foveal vascular density (FVD) in the SCP than control eyes, while in the DCP, FVD was lower in the degenerative LMH eyes relative to the other groups. Conclusion. The finding of microvascular changes between degenerative and tractional LMH subtypes highlights their distinct pathologies and supports recent changes in the classification and terminology of this macular condition.